Perinatal fetal loss grief counselling experience for expectant fathers: a qualitative study - Gao, Qiong; Zhu, Lili; Guo, Hua; Zhu, Zhiling; Zhang, Fuqin; Wang, Yiqin; Hou, Beijie (Frontiers in Psychiatry, 2025)
BackgroundExpectant fathers may experience negative emotions such as grief and distress following perinatal fetal death, potentially sustaining psychological trauma of varying severity. In severe cases, this may adversely affect family harmony, marital intimacy, and social cohesion. Consequently, understanding fathers’ experiences within such circumstances is of paramount importance.Aims and objectivesTo explore the experience of grief counselling for expectant fathers following perinatal fetal loss.MethodsSixteen expectant fathers who experienced perinatal fetal loss were recruited for semi-structural interviews between January and December 2024 from a tertiary hospital in Xinxiang, Henan. Transcripts of interviews were analyzed using the Colaizzi 7-step analysis method.ResultsThree themes and nine sub-themes were identified, including the need for grief counselling (hidden self-needs and needs corresponding to psychological development stages), the coexistence of negative and positive emotions (pain, sorrow, helplessness, frustration, acceptance, blessings, and prayers), and the desire for support (emotional support, medical support, and positive self-identity).ConclusionNursing staff should accurately assess the grief counselling needs of fathers who have experienced perinatal fetal loss, and provide them with multifaceted support to alleviate negative emotions. It is recommended that healthcare organizations form multidisciplinary professional teams to provide support and assistance to fathers to help them positively cope with negative emotions and future life and to promote the development of perinatal grief counselling.